Homeogenomics: Unraveling Genetic Regulation and Therapeutic Potential - Mordeniz, Cengiz (Medical Science: Trends and Innovations Vol. 11, 2025)
Homeogenomics primarily focuses on understanding the interactions between homoeopathic remedies and the genetic blueprint or genome. This involves the identification of which gene or genes are targeted by a particular remedy. A new area of research has been raised to explore the possibility of developing a personalized remedy selection procedure by application of molecular homeogenomics. The application of personalized medicine in medical practice requires the study of the human genome with regard to drug pharmacokinetics, pharmacodynamics, interactions and tolerance profile. The consideration of gene × environment interactions and the inclusion of “omics’ ‘data in pharmacogenomic studies of drugs will facilitate the generation of reliable results and will promote tailored treatments and new strategies of research and development. Pharmacogenetics is the search for genetic polymorphisms that affect responses to drug therapy and refers to the study of variations in a single gene, whereas pharmacogenomics is the study of variations in multiple genes and the basis of personalisation of treatment to allow higher medication success rates. This study proposes a philosophical–scientific correlation between homeopathic remedies and epigenetic modifications as homeopathic medicine being also a modulator of gene expression. Based on the study of homeopathic doctrine and epigenetics, a conceptual and functional correlation is observed between homeopathic remedies and epigenetic modifications. Homeopathic remedies act on the Genome by modulating gene expression. Several experimental studies suggest that homeopathy’s mechanism of action may be by modulating gene expression. According to modern genetics, epigenetic alterations are the fundamental cause of the manifestation of chronic diseases as well as therapeutic modulator of gene expression for their management. Homeopathic remedies may act on the epigenetic expression of the individual to heal personally and holistically.